2017
DOI: 10.1080/15287394.2017.1408201
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pulmonary responses in mice to asbestos/asbestiform fibers using gene expression profiles

Abstract: Humans exposed to asbestos and/or asbestiform fibers are at high risk of developing many lung diseases including asbestosis, lung cancer, and malignant mesothelioma. However, the disease-causing potential and specific metabolic mechanisms and pathways associated with various asbestos/asbestiform fiber exposures triggering different carcinogenic and non-carcinogenic outcomes are still largely unknown. The aim of this this study was to investigate gene expression profiles and inflammatory responses to different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 75 publications
0
6
0
1
Order By: Relevance
“…fumigatus and other fungal species . The immune system of healthy individuals, namely the alveolar macrophages and neutrophils, is able to dispose of inhaled conidia ,,, These are the same cells which are known to be activated as the body’s response to exposure with nanoparticles (NPs). − Yet, effective strategies to improve the outcome for patients with invasive mycoses represent an enormous medical challenge.…”
Section: Introductionmentioning
confidence: 99%
“…fumigatus and other fungal species . The immune system of healthy individuals, namely the alveolar macrophages and neutrophils, is able to dispose of inhaled conidia ,,, These are the same cells which are known to be activated as the body’s response to exposure with nanoparticles (NPs). − Yet, effective strategies to improve the outcome for patients with invasive mycoses represent an enormous medical challenge.…”
Section: Introductionmentioning
confidence: 99%
“…3.5), and it is this needle-like structure that makes asbestos highly invasive and persistent, especially in the lungs. The pathways by which asbestos causes lung diseases are not fully understood, however it is widely reported that asbestos induces inflammation, tissue damage, and DNA and chromosomal damage (Nymark et al 2008;Yanamala et al 2018). Research efforts into the mechanisms for the asbestos induced disease are ongoing, and key breakthroughs in understanding the pathogenesis of diseases associated with this mineral fibre will allow for important progress in the prevention and treatment of asbestosrelated diseases.…”
Section: Asbestos: From "Magicmentioning
confidence: 99%
“…A recent study has reported the genes that were differentially expressed in lungs of mice exposed to crocidolite and erionite fibers compared to a control group (54). Crocidolite and erionite are asbestos or asbestos-like particles that are capable of inducing lung cancer and/or mesothelioma in humans and animal models (54).…”
Section: Analysis With Other High-throughput Datamentioning
confidence: 99%
“…A recent study has reported the genes that were differentially expressed in lungs of mice exposed to crocidolite and erionite fibers compared to a control group (54). Crocidolite and erionite are asbestos or asbestos-like particles that are capable of inducing lung cancer and/or mesothelioma in humans and animal models (54). Out of the 1,710 genes differentially expressed on crocidolite exposure, 160 genes were part of the MPM interactome (p-value of overlap =3.63E-05), and 6 out of 78 genes differentially expressed on erionite exposure occured in the MPM interactome ( Figure 4 and Data File 3).…”
Section: Analysis With Other High-throughput Datamentioning
confidence: 99%